Further cranial settling of the upper cervical spine following odontoidectomy - Report of two cases - (:unkn) unknown (AMER ASSOC NEUROLOGICAL SURGEONS, 2001)
A variety of diseases may affect the craniovertebral junction and require a decompressive and fusion procedure. Craniovertebral junction instability is expected after a fusion procedure. The authors describe two patients with basilar invagination who underwent transoral odontoidectomy and occipitocervical fixation. Despite an uneventful immediate postoperative course, further cranial settling of the C-2 vertebral body (VB) was demonstrated. One patient experienced neurological deterioration and required a second decompressive procedure, whereas the second patient was asymptomatic and required no additional surgery. It was concluded that the odontoidectomy may have led to horizontal separation of the C-1 lateral masses, resulting in further cranial settling of the C-2 VB, Preservation of one aspect of the C-1 anterior arch minimizes C-1 lateral mass offset and, in turn, further cranial settling of the C-2 VB. In addition, a more rigid fixation of C-2 may minimize the possibility of horizontal separation of the C-1 lateral masses after transoral odontoidectomy.
Keywords: basilar invagination; cranial settling; odontoidectomy; transoral approach; FIXATION; FUSION; INSTRUMENTATION; PLATE